Anastasios Sinaites: Byzantinisches Christentum in den ersten Jahrzehnten unter arabischer Herrschaft - Uthemann, Karl-Heinz (De Gruyter eBook-Paket Theologie, Religionswissenschaften, Judaistik, 2015)
At long last, this book provides a comprehensive study of the life and work of the 7th century monk and theologian Anastasius Sinaïta (Anastasios of Sinai). It analyzes his principal work, the Hodegos (or Viae Dux) and his other Christological writings, and also presents his sermons and his role as an apologist toward the Jews and Moslems and an exegetist of Genesis 1–3.